Mothers Community, COVID-19, and Family Resilience - Monika Sri Yuliarti (COMMUNICATION MAJOR, 2023)
The COVID-19 pandemic has had a huge impact on all aspects of human life. One of the things that changed drastically during the crisis was the change in human activities from offline to online. This happened because of the physical distancing policy that was enforced to prevent the spread of the virus. One of the things that is challenged is family resilience. This study aims to explore the role of women in the family, in relation to family resilience during the COVID-19 pandemic crisis, by specifically conducting studies on the ‘Ibu Profesional’ community. As a country where patriarchal values are still attached, in Indonesia, women are always placed exclusively in the private sphere and do not receive respect because of this position. Nevertheless, it is very interesting to explore the extent to which the private sphere contributes to family resilience in times of crisis. By conducting interviews with 6 members of the community from the Surakarta branch, Indonesia, this research yielded the following findings: (1) Women play an important role in family resilience during the COVID-19 pandemic, both in the private and public spheres: (2) Women have the ability to master technology internet due to the changing mode of community activity from offline to online. Furthermore, they also prefer online activities compared to offline activities because of its simplicity.